Factors influencing organizational commitment of banking sector employees - Sowmya, K. R. (Journal of Economics and Behavioral Studies, 2011)
Organizational Commitment has been conceptualised & measured in different ways. This study is an attempt to identify the factors influencing organizational commitment of banking sector employees in Chennai. It is also important as suggestions can be given to the banking sector in order to bring an awareness of the commitment level of employees. Gaining awareness of commitment level and the respective influencing factor will help concentrate on increasing the commitment of employees. Using the measures developed by Mowday; Steers and Porter, the researchers have exploited Factor analysis by Principle Component Method to identify the factors influencing the organizational commitment of employees of PSBs and NPSBs.